Readmission and reoperation rates after resection of malignant primary brain tumours in England 2013-2017. (15th October 2021) - Wahba, Adam; Phillips, Nick; Hutchinson, Peter; Cromwell, David; Mathew, Ryan
Abstract: Aims: Morbidity and mortality following resection of malignant primary brain tumours is high. The benefits of reoperation for recurrent tumours are uncertain and it is not known how frequently patients in England undergo further tumour resections. The aim of this study was to describe 30-day and one-year readmission rates, the clinical reasons for readmission and the rate of resections for recurrent tumours. Method: Patient data was extracted from Hospital Episode Statistics (the hospital administrative data for NHS hospitals in England) for all supratentorial, malignant, primary brain tumour resections performed from April 2013 to March 2017. All subsequent non-elective readmissions to any NHS hospital and all readmissions for further tumour resection within 30 days and one year were analysed for the primary clinical diagnosis and primary procedure performed. Results: A total of 6, 982 patients were identified and the 30-day and one-year readmission rates were 18.6% (n=1, 298) and 57.4% (n=4, 007), respectively. The rates of reoperation for tumour resection were 0.5% (n=33) and 6.2% (n=432), respectively. The commonest reasons for 30-day readmission were post-operative complications (17.9% of admissions), general medical complications (17.3%) and surgical site infection (9.6%). The most frequently performed neurosurgical procedures were for treatment of surgical site infection (37.6% of procedures). The commonest reasons for readmission within one year were general medical complications (17.4%), seizures (14%), systemic infections (11.4%) and post-operative complications (11%). Almost half of all neurosurgical procedures performed within one year were reoperation for tumour resection (45.6%), while treatment of surgical site infection (17.9%) and CSF shunt insertions and revisions (9.1%) were also common. Conclusion: This study provides a descriptive analysis of the rates of readmission, diagnosis on readmission, and the need for further neurosurgical procedures. The rate of non-elective readmissions within one year is high and these data may be useful for service planning and for counselling patients about their treatment. Additionally, these data contribute to the development of quality indicators, for benchmarking and comparing quality of care provision between neurosurgical units. Further research, with linkage to histology data and performance status, would support an analysis of the role of resection of recurrent, malignant, primary brain tumours.